High-strength and high-toughness composite plastic tray and preparation method thereof

By using specific ratios of high-density polyethylene, linear low-density polyethylene and appropriate toughening agents, high-strength and high-toughness composite plastic pallets are prepared, which solves the shortcomings of existing pallets in terms of mechanical strength and impact toughness. , achieving higher volume of cargo and better logistics performance.

CN119431949APending Publication Date: 2025-02-14ZHEJIANG SHENYUAN INTELLIGENT MANUFACTURING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411549180.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing plastic pallets have shortcomings in terms of high mechanical strength and impact toughness, resulting in limited cargo volume transported in a single day, which is unable to meet the higher requirements of modern logistics for pallet performance.

Method used

High-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength high-strength Tough composite plastic pallet.

Benefits of technology

It improves the mechanical strength and impact toughness of plastic pallets, reduces the density of pallets, meets the needs of lightweight, and thus improves the volume of goods transported per day and improves the logistics level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of plastic products, in particular to a high-strength and high-toughness composite plastic tray and a preparation method thereof. The invention discloses a high-strength and high-toughness composite plastic tray. The high-density polyethylene composite material is prepared from the following raw materials in percentage by mass: 20 to 40 percent of high-density polyethylene (HDPE), 0 to 5 percent of linear low-density polyethylene (LLDPE), 3 to 6 percent of compatilizer composition, 5 to 20 percent of flexibilizer composition, 1 to 5 percent of toughening and reinforcing filler composition, 0.5 to 2 percent of silicone master batch, 1 to 3 percent of anti-aging aid, 0.5 to 1.0 percent of rheological master batch and the balance of polypropylene (PP). The flexibilizer composition is polyurethane with a core-shell structure, and the core of the polyurethane with the core-shell structure is polyurethane (PU). The plastic tray is low in density, meets the requirement for light weight, has the advantages of being high in stacking limit load and impact toughness, and can improve the quantity of goods transported every day, so that the logistics level is improved, and economic development is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of plastic products, and in particular to a high-strength and high-toughness composite plastic pallet and a preparation method thereof. Background Art

[0002] Plastic pallets are generally made of polypropylene PP and high-density polyethylene HDPE. They have the advantages of good mechanical properties, light weight, non-toxicity, easy processing, easy disinfection, corrosion resistance, etc. They are widely used in production, transportation, warehousing and circulation. In modern logistics, the number of plastic pallets, the development of production technology and the depth of performance research are important indicators of a country's logistics level. This is mainly because plastic pallet intermodal transport has the advantages of saving labor, time, safety, efficiency, reducing cargo packaging costs, and saving storage and stacking area.

[0003] With the rapid development of modern logistics, the amount of goods transported per day is constantly increasing, and higher requirements are put forward for the mechanical strength (bending strength, stacking limit load), impact toughness and service life of plastic pallets. Chinese patent CN113549291B discloses a creep-resistant polypropylene and its preparation method and plastic pallet, including the following polypropylene 45-76 parts, maleic anhydride 3-8 parts, initiator 1-4 parts, polytetrafluoroethylene particles 0.8-2 parts, 2,2,6,6-tetramethyl-1-(1-phenylethoxy) piperidine 0.02-0.2 parts, glass fiber 11-23 parts, dispersant 1-3 parts, creep-resistant modifier 13-21 parts, creep-resistant modifier is composed of barium sulfate, calcium carbonate and carbon black according to the mass ratio of 2:5:3.

[0004] In the above-mentioned prior art solutions, glass fiber is used to improve the overall tensile strength, while improving the overall heat resistance and aging resistance, and has the effect of delaying aging for pallets exposed to the sun for a long time; calcium carbonate, carbon black, and barium sulfate are used to further improve the creep resistance of polypropylene. However, the high content of fillers (glass fiber, calcium carbonate, carbon black, barium sulfate) in the formula of the plastic pallet makes the density of the prepared plastic pallet relatively large, and the overall quality of the plastic pallet increases. Under the condition of constant freight volume, the plastic pallet limits the cargo carrying capacity.

[0005] To this end, the inventor provides a high-strength and high-toughness composite plastic pallet and a preparation method thereof. Summary of the invention

[0006] In order to solve the above-mentioned problems existing in the prior art, the present application provides a high-strength and high-toughness composite plastic pallet and a preparation method thereof, which can increase the amount of cargo transported per day, thereby improving the level of logistics and promoting economic development.

[0007] The high-strength and high-toughness composite plastic pallet provided in this application is realized through the following technical solutions:

[0008] A high-strength and high-toughness composite plastic pallet is made of the following raw materials in percentage by mass: 20-40% high-density polyethylene HDPE, 0-5% linear low-density polyethylene LLDPE, 3-6% compatibilizer composition, 5-20% toughening agent composition, 1-5% toughening and reinforcing filler composition, 0.5-2% silicone masterbatch, 1-3% anti-aging additive, 0.5-1.0% rheological masterbatch, and the balance is polypropylene PP;

[0009] The compatibilizer composition is at least one of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH;

[0010] The toughening agent composition is a core-shell structured polyurethane, wherein the shell of the core-shell structured polyurethane is one or a combination of acrylonitrile-styrene-butadiene copolymer ABS and maleic anhydride grafted polystyrene PS, and the core is polyurethane PU;

[0011] The toughening and reinforcing filler composition comprises at least one of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with ABS resin modified, and ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with PS resin modified, in combination with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0012] In the present application, the core-shell structured polyurethane is used as a toughening agent composition to effectively improve the impact resistance of the finished plastic pallet; a specific compatibilizer composition is used to improve the compatibility of the toughening agent composition, the toughening and reinforcing filler composition and the matrix resin, thereby improving the overall mechanical strength and impact resistance; a specific toughening and reinforcing filler composition is used and its addition amount is controlled to meet the lightweight requirements of the finished plastic pallet, while imparting excellent mechanical strength and impact resistance.

[0013] In summary, the plastic pallet in this application has a low density, meets the lightweight requirements, and has the advantages of high stacking limit load and impact resistance, which can increase the amount of cargo transported per day, thereby improving logistics levels and promoting economic development.

[0014] Preferably, when the core-shell polyurethane is acrylonitrile-styrene-butadiene copolymer ABS, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH;

[0015] When the core-shell polyurethane is polystyrene PS, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH;

[0016] When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, or maleic anhydride grafted polystyrene PS-g-MAH.

[0017] Preferably, when the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, the mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2);

[0018] When the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH, the mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2);

[0019] When the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH, the mass ratio of the maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.02-0.10):(0.02-0.10)

[0020] By adopting the above technical solution, the mechanical strength and impact resistance of the prepared plastic pallet can be improved.

[0021] Preferably, when the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition includes at least one of surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes;

[0022] When the shell of the core-shell polyurethane is polystyrene PS, the toughening and reinforcing filler composition includes at least one of the following: an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified surface, a surface-nonpolar modified boron nitride whisker, a surface-nonpolar modified potassium titanate whisker, a surface-nonpolar modified zinc oxide whisker, a surface-magnetic ferroferric oxide grafted boron nitride whisker, a surface-magnetic ferroferric oxide grafted potassium titanate whisker, a surface-magnetic ferroferric oxide grafted zinc oxide whisker, and a surface-magnetic ferroferric oxide grafted halloysite nanotube;

[0023] When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes at least one of a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, a surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, and a surface non-polar modified boron nitride whisker, a surface non-polar modified potassium titanate whisker, a surface non-polar modified zinc oxide whisker, a surface magnetic ferroferric oxide grafted boron nitride whisker, a surface magnetic ferroferric oxide grafted potassium titanate whisker, a surface magnetic ferroferric oxide grafted zinc oxide whisker, and a surface magnetic ferroferric oxide grafted halloysite nanotube.

[0024] Preferably, when the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition includes at least one of surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, and surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes;

[0025] When the shell of the core-shell polyurethane is polystyrene PS, the toughening and reinforcing filler composition includes at least one of surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface-nonpolar modified boron nitride whiskers, surface-nonpolar modified potassium titanate whiskers, and surface-nonpolar modified zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted boron nitride whiskers, surface-magnetic ferroferric oxide-grafted potassium titanate whiskers, surface-magnetic ferroferric oxide-grafted zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted halloysite nanotubes;

[0026] When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, in combination with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, in combination with at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0027] Preferably, when the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface;

[0028] When the core-shell polyurethane shell is polystyrene PS, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface;

[0029] When the toughening agent composition is a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modifications, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface.

[0030] By adopting the above technical solution, the mechanical strength and impact resistance of the prepared plastic pallet can be further improved.

[0031] Preferably, when the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and modified by ABS resin on the surface, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface, the mass ratio of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and modified by ABS resin on the surface, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface is 100:(10-30):(10-50);

[0032] When the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface, the mass ratio of the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface is 100:(10-30):(10-50);

[0033] When the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface non-polar modified potassium titanate whiskers, and surface magnetic ferroferric oxide grafted potassium titanate whiskers, the mass ratio of the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, the surface non-polar modified potassium titanate whiskers, and the surface magnetic ferroferric oxide grafted potassium titanate whiskers is (40-60):(40-60):(10-30):(10-50).

[0034] By adjusting the composition and ratio of toughening and reinforcing fillers, the mechanical strength and impact resistance of the prepared plastic pallet can be improved.

[0035] Preferably, the toughening and reinforcing filler composition also includes ABS@PU@inorganic whiskers, and the inorganic whiskers in the ABS@PU@inorganic whiskers include at least one of boron nitride whiskers, surface potassium titanate whiskers, zinc oxide whiskers, zirconium oxide whiskers, silicon carbide whiskers, and calcium carbonate whiskers.

[0036] By adopting the above technical solution, the mechanical strength and impact resistance of the prepared plastic pallet can be further improved.

[0037] Preferably, the silicone masterbatch is at least one of CMB1502 / polyethylene carrier silicone masterbatch, CMB1501 / polypropylene carrier silicone masterbatch, and CMB901 / automotive interior PP scratch-resistant masterbatch; the rheological masterbatch is CDM2022 / rheological masterbatch; the anti-aging additive includes an antioxidant and an anti-ultraviolet agent, and the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 1024 combined with at least one of antioxidant 168 and antioxidant 697; the anti-ultraviolet agent is at least one of UV-531, UV-234, and UV-622.

[0038] By adopting the above technical solution, the weather resistance and easy processing and demoulding performance of the prepared plastic pallet can be further improved.

[0039] The present application provides a method for preparing a high-strength and high-toughness composite plastic pallet, which is achieved through the following technical solutions:

[0040] A method for preparing a high-strength and high-toughness composite plastic pallet comprises the following steps:

[0041] Step 1, placing accurately measured high-density polyethylene, linear low-density polyethylene, compatibilizer composition, toughening agent composition, silicone masterbatch, rheological masterbatch, polypropylene, and anti-aging additive at 160-165° C. and kneading for 240-320 seconds to obtain a mixture;

[0042] Step 2: Put the mixture and the toughening and reinforcing filler composition into a twin-screw extruder for melt extrusion, wire drawing, cooling, granulation, and drying to obtain a plastic pallet masterbatch with a particle size of 0.5-2.0 mm;

[0043] Step 3: Put the plastic pallet masterbatch into a twin-screw extruder for melt extrusion, and inject the obtained melt extrusion into a molding die. The temperature of the molding die is controlled at 140-160°C, and a magnetic field is applied. The magnetic field strength is 300-1200mT, and the direction of the magnetic field is relatively perpendicular to the horizontal plane of the molding die. The magnetic field holding time is 2-8h, and the semi-finished pallet is naturally cooled to room temperature to obtain a semi-finished pallet;

[0044] Step 4: heat treat the semi-finished pallet in the molding mold of step 3 to eliminate internal stress. Apply a magnetic field with a magnetic field strength of 300-1200mT. The direction of the magnetic field is relatively perpendicular to the horizontal plane of the molding mold. Heat the temperature to 80-120℃ at a rate of 0.5-1℃ / min for 0.5-1h. Open the furnace and cool naturally to room temperature. Demould, trim burrs, and grind to obtain a finished plastic pallet.

[0045] In the preparation method of the present application, an external magnetic field is used to adjust the distribution state of the surface magnetic ferroferric oxide grafted inorganic material in the toughening and reinforcing filler composition, so that the radial direction of part of the surface magnetic ferroferric oxide grafted inorganic material changes under the action of the external magnetic field and becomes parallel to the direction of the external magnetic field or reduces the angle between the radial and vertical planes of the surface magnetic ferroferric oxide grafted inorganic material, thereby improving the stacking limit load performance and static / dynamic load capacity of the finished plastic pallet.

[0046] The preparation method of the plastic pallet provided in the present application is relatively simple and has low operating difficulty, which is convenient for industrial production, reduces the price of the finished plastic pallet, and facilitates market promotion and application.

[0047] In summary, this application has the following advantages:

[0048] 1. The plastic pallet in this application has a low density, meets the lightweight requirements, and has the advantages of high stacking limit load and impact resistance, which can increase the amount of cargo transported per day, thereby improving the logistics level and promoting economic development.

[0049] 2. The core-shell structured polyurethane used as the toughening agent composition in this application can effectively improve the overall impact toughness.

[0050] 3. The present application adopts a specific compatibilizer composition to improve the compatibility of the toughening agent composition, the toughening and reinforcing filler composition and the matrix resin, thereby improving the overall mechanical strength and impact toughness.

[0051] 4. The specific toughening and reinforcing filler composition used in the present application and the amount of the toughening and reinforcing filler composition added are controlled, which can not only meet the lightweight requirements of the finished plastic pallet, but also give the plastic pallet excellent mechanical strength and impact resistance.

[0052] 5. The preparation method of the present application is relatively simple, has low operating difficulty, and is easy to implement industrial production.

[0053] 6 In the preparation method of the present application, the radial direction of the surface magnetic ferroferric oxide grafted inorganic material is adjusted, which can effectively improve the overall stacking limit load performance and static / dynamic load capacity of the plastic pallet while ensuring the excellent mechanical strength and impact resistance of the plastic pallet. DETAILED DESCRIPTION

[0054] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0055] Example

[0056] A high-strength and high-toughness composite plastic pallet is made of the following raw materials in percentage by mass: 20-40% of high-density polyethylene (HDPE), 0-5% of linear low-density polyethylene (LLDPE), 3-6% of a compatibilizer composition, 5-20% of a toughening agent composition, 1-5% of a toughening and reinforcing filler composition, 0.5-2% of a silicone masterbatch, 1-3% of an anti-aging aid, 0.5-1.0% of a rheological masterbatch, and the balance is polypropylene (PP).

[0057] Preferably, a high-strength and high-toughness composite plastic pallet is made of the following raw materials in percentage by mass: 30-35% high-density polyethylene HDPE, 2-3% linear low-density polyethylene LLDPE, 4-5% compatibilizer composition, 8-12% toughening agent composition, 2-4% toughening and reinforcing filler composition, 0.8-1.5% silicone masterbatch, 1.8-2.6% anti-aging additive, 0.6-0.8% rheological masterbatch, and the balance is polypropylene PP.

[0058] The compatibilizer composition is at least one of maleic anhydride grafted polyethylene HDPE-g-MAH (HDPE grafted maleic anhydride of Coais Chemical Co., Ltd., brand W1H), maleic anhydride grafted polypropylene PP-g-MAH (PP-g-MAH of Coais Chemical Co., Ltd., brand B1A) with maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH (LLDPE grafted maleic anhydride of Coais Chemical Co., Ltd., brand W1L), maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH (ABS-G-MAH maleic anhydride toughener of Dongguan Shengli New Materials Co., Ltd., model: XH21605SIYKN), and maleic anhydride grafted polystyrene PS-g-MAH (maleic anhydride grafted PS-G-MAH of Dongguan Shengli New Materials Co., Ltd., brand M400A, model XH216012TUBU).

[0059] When the raw materials for preparing the plastic pallet contain linear low-density polyethylene LLDPE, the compatibilizer composition also contains maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, that is, the compatibilizer composition is composed of at least one of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH combined with maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH.

[0060] The toughening and reinforcing filler composition comprises at least one of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with ABS resin modified, and ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with PS resin modified, in combination with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0061] When the shell of the core-shell polyurethane is acrylonitrile-styrene-butadiene copolymer ABS, the compatibilizer composition is maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH; the mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2).

[0062] When the shell of the core-shell polyurethane is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition includes at least one of surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0063] Preferably, the toughening and reinforcing filler composition comprises an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated ABS resin-modified surface, combined with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, combined with at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0064] Further preferably, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface in a mass ratio of 100:(10-30):(10-50).

[0065] When the core-shell polyurethane has a shell composed of polystyrene PS, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH. The mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2). The toughening and reinforcing filler composition includes an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified fiber, and is matched with at least one of a surface non-polar modified boron nitride whisker, a surface non-polar modified potassium titanate whisker, a surface non-polar modified zinc oxide whisker, a surface magnetic ferroferric oxide grafted boron nitride whisker, a surface magnetic ferroferric oxide grafted potassium titanate whisker, a surface magnetic ferroferric oxide grafted zinc oxide whisker, and a surface magnetic ferroferric oxide grafted halloysite nanotube.

[0066] Preferably, the toughening and reinforcing filler composition comprises an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified surface, combined with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, combined with at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0067] Further preferably, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface in a mass ratio of 100:(10-30):(10-50).

[0068] When the toughening agent composition is composed of a polyurethane with a core-shell structure of acrylonitrile-styrene-butadiene copolymer ABS as the shell and a polyurethane with a core-shell structure of polystyrene PS as the shell, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH. The mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.02-0.10):(0.02-0.10).

[0069] The toughening and reinforcing filler composition includes at least one of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, and surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0070] Preferably, the toughening and reinforcing filler composition comprises an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, a surface-coated PS resin modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, and at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, and at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

[0071] Further preferably, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface in a mass ratio of (40-60):(40-60):(10-30):(10-50).

[0072] A method for preparing a high-strength and high-toughness composite plastic pallet comprises the following steps:

[0073] Step 1, placing accurately measured high-density polyethylene, linear low-density polyethylene, compatibilizer composition, toughening agent composition, silicone masterbatch, rheological masterbatch, polypropylene, and anti-aging additive at 160-165° C. and kneading for 240-320 seconds to obtain a mixture;

[0074] Step 2: Put the mixture and the toughening and reinforcing filler composition into a twin-screw extruder for melt extrusion, wire drawing, cooling, granulation, and drying to obtain a plastic pallet masterbatch with a particle size of 0.5-2.0 mm;

[0075] When the toughening and reinforcing filler composition does not contain at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes, then in step three, the plastic pallet masterbatch is put into a twin-screw extruder for melt extrusion, the obtained melt extrusion is injected into a molding mold, and naturally cooled to room temperature to obtain a semi-finished pallet; in step four, the semi-finished pallet in the molding mold of step three is heat-treated to eliminate internal stress, the temperature is increased to 80-120°C at 0.5-1°C / min for heat treatment for 0.5-1h, the furnace is opened and naturally cooled to room temperature, and the finished plastic pallet is obtained by demolding, trimming burrs, and polishing;

[0076] When the toughening and reinforcing filler composition contains at least one of boron nitride whiskers grafted with surface magnetic ferroferric oxide, potassium titanate whiskers grafted with surface magnetic ferroferric oxide, zinc oxide whiskers grafted with surface magnetic ferroferric oxide, and halloysite nanotubes grafted with surface magnetic ferroferric oxide, then in step three, the plastic pallet masterbatch is put into a twin-screw extruder for melt extrusion, and the obtained melt extrusion is injected into a molding mold, the temperature of the molding mold is controlled to be 140-160°C, a magnetic field is applied, and the magnetic field strength is 300-1200m T, the direction of the magnetic field is relatively perpendicular to the horizontal plane of the forming mold, the magnetic field holding time is 2 to 8 hours, and the semi-finished pallet is naturally cooled to room temperature; step four, the semi-finished pallet in the forming mold of step three is heat treated to eliminate internal stress, under the application of a magnetic field, the magnetic field strength is 300-1200mT, the magnetic field direction is relatively perpendicular to the horizontal plane of the forming mold, the temperature is increased to 80-120℃ at 0.5-1℃ / min, heat treated for 0.5-1h, the furnace is opened and naturally cooled to room temperature, demoulding, trimming burrs, and polishing to obtain a finished plastic pallet.

[0077] Preparation Example 1: A method for preparing a core-shell polyurethane toughening material with PS as a shell, comprising the following steps:

[0078] Step 1: 500.5 g of MDI, 67.1 g of dimethylol propionic acid, 400 g of polycarbonate diol CD220 (molecular weight 2000, Japan Daicel Corporation), 600 g of polyethylene adipate diol (molecular weight 2000, Zhejiang Hexin Technology Co., Ltd.), 67.1 g of dimethylol propionic acid, 8 g of antioxidant 1010, and 100 g of acetone are added to a reactor equipped with an acetone condensation reflux device and a pressure relief device, and the temperature is raised to 85° C. under nitrogen protection, and 0.84 g of dibutyl dilaurate is added. Tin was reacted for 2 hours, and then 106.4g of 1,6-hexanediol was added to continue to react at 80°C for 2 hours to obtain a polyurethane prepolymer. 19.6g of hydroxyethyl methacrylate was added to the polyurethane prepolymer and reacted at 80°C for 1 hour until the NCO content of the system was 0, and then 160g of acetone was added, and the system viscosity was adjusted to 5450mPa.s. After the reaction was completed, the temperature was lowered to 35°C, and dimethylethanolamine was added to neutralize for 5 minutes. Under high-speed shearing of a shear disperser, 800g of deionized water was added to disperse, and an aqueous polyurethane resin emulsion was obtained;

[0079] Step 2, preparing a hydrocarbon phase solution: 400 g of styrene PS, 36 g of sodium p-styrene sulfonate, 2.6 g of azobisisobutyronitrile, and 800 g of deionized water are mixed and emulsified under high-speed shearing in a shear disperser to obtain a styrene emulsion;

[0080] Step 3: The waterborne polyurethane resin emulsion is heated to 85° C., and the styrene emulsion prepared in step 2 is added dropwise at a dropping speed of 50 g / min. After the addition is completed, the reaction is continued for 45 minutes until the concentration of the styrene monomer is lower than 0.1wt%. The temperature is lowered to 55° C., 1000 g of deionized water is added, and emulsified and dispersed under high-speed shearing of a shear disperser. The acetone is then removed in vacuo to obtain a modified polyurethane dispersion. The average particle size of the emulsion is 350 nm. The emulsion is spray-dried to obtain a core-shell structure polyurethane toughening material.

[0081] Preparation Example 2: A method for preparing a core-shell structure polyurethane toughening material with PS as a shell, comprising the following steps:

[0082] Step 1: 500.5 g of MDI, 67.1 g of dimethylol propionic acid, 300 g of polycarbonate diol CD220 (molecular weight 2000, Japan Daicel Corporation), 600 g of polyethylene adipate diol (molecular weight 2000, Zhejiang Hexin Technology Co., Ltd.), 127.5 g of hydroxy-terminated polybutadiene HTPB (HTPB-II of Shandong Zibo Qilong Chemical Co., Ltd., data molecular weight 2300-2800, hydroxyl group 0.8-1.0 mmol / g), 80.5 g of dimethylol propionic acid, 8 g of antioxidant 1010, and 100 g of acetone are added to a condenser equipped with an acetone reflux device and a discharge device. In a reactor of a pressure device, the temperature was raised to 85°C under nitrogen protection, 0.84g of dibutyltin dilaurate was added and reacted for 2h, and then 72.1g of 1,4-butanediol was added and continued to react at 80°C for 2h to obtain a polyurethane prepolymer, 23.2g of hydroxyethyl methacrylate was added to the polyurethane prepolymer and reacted at 80°C for 1h until the NCO content of the system was 0, and then 160g of acetone was added, and the viscosity of the system was adjusted to 5670mPa.s. After the reaction was completed, the temperature was lowered to 35°C, dimethylethanolamine was added to neutralize for 5min, and 800g of deionized water was added to disperse under high-speed shearing of a shear disperser to obtain an aqueous polyurethane resin emulsion;

[0083] Step 2, preparing a hydrocarbon phase solution: 420 g of styrene PS, 36 g of sodium p-styrene sulfonate, 2.7 g of azobisisobutyronitrile, and 800 g of deionized water are mixed and then emulsified under high-speed shearing of a shear disperser to obtain a styrene emulsion;

[0084] Step 3: The waterborne polyurethane resin emulsion is heated to 85° C., and the styrene emulsion prepared in step 2 is added dropwise at a dropping speed of 50 g / min. After the addition is completed, the reaction is continued for 45 minutes until the concentration of the styrene monomer is lower than 0.1wt%. The temperature is lowered to 55° C., 1000 g of deionized water is added, and the mixture is emulsified and dispersed under high-speed shearing of a shear disperser. The acetone is then removed in vacuo to obtain a modified polyurethane dispersion. The average particle size of the emulsion is 400 nm. The emulsion is spray-dried to obtain a core-shell structure polyurethane toughening material.

[0085] Preparation Example 3: A method for preparing a core-shell structure polyurethane toughening material with ABS as a shell, comprising the following steps:

[0086] Step 1: 500.5 g of MDI, 67.1 g of dimethylol propionic acid, 400 g of polycarbonate diol CD220 (molecular weight 2000, Japan Daicel Corporation), 600 g of polyethylene adipate diol (molecular weight 2000, Zhejiang Hexin Technology Co., Ltd.), 67.1 g of dimethylol propionic acid, 8 g of antioxidant 1010, and 100 g of acetone are added to a reactor equipped with an acetone condensation reflux device and a pressure relief device, and the temperature is raised to 85° C. under nitrogen protection, and 0.84 g of dibutyl dilaurate is added. Tin was reacted for 2 hours, and then 106.4g of 1,6-hexanediol was added to continue to react at 80°C for 2 hours to obtain a polyurethane prepolymer. 19.6g of hydroxyethyl methacrylate was added to the polyurethane prepolymer and reacted at 80°C for 1 hour until the NCO content of the system was 0, and then 160g of acetone was added, and the system viscosity was adjusted to 5450mPa.s. After the reaction was completed, the temperature was lowered to 35°C, and dimethylethanolamine was added to neutralize for 5 minutes. Under high-speed shearing of a shear disperser, 800g of deionized water was added to disperse, and an aqueous polyurethane resin emulsion was obtained;

[0087] Step 2, preparing a hydrocarbon phase solution: 180 g of styrene PS, 120 g of butadiene, 100 g of acrylonitrile, 10 g of butyl methacrylate, 36 g of sodium p-styrene sulfonate, 0.5 g of cumene hydroperoxide, 1 g of tert-dodecyl mercaptan, and 1000 g of deionized water are mixed and emulsified under high-speed shearing in a shear disperser to obtain an ABS emulsion;

[0088] Step 3: The waterborne polyurethane resin emulsion is heated to 85° C., and the ABS emulsion prepared in step 2 is added dropwise at a dropping speed of 50 g / min. After the addition is completed, the reaction is continued for 60 minutes until the styrene monomer concentration is lower than 0.1wt%. The temperature is lowered to 55° C., 1000 g of deionized water is added, and emulsified and dispersed under high-speed shearing of a shear disperser. The acetone is then removed in vacuo to obtain a modified polyurethane dispersion. The average particle size of the emulsion is 350 nm. The emulsion is spray-dried to obtain a core-shell structure polyurethane toughening material.

[0089] Preparation Example 4: A method for preparing a core-shell structure polyurethane toughening material with ABS as a shell, comprising the following steps:

[0090] Step 1: 500.5 g of MDI, 67.1 g of dimethylol propionic acid, 300 g of polycarbonate diol CD220 (molecular weight 2000, Japan Daicel Corporation), 600 g of polyethylene adipate diol (molecular weight 2000, Zhejiang Hexin Technology Co., Ltd.), 127.5 g of hydroxy-terminated polybutadiene HTPB (HTPB-II of Shandong Zibo Qilong Chemical Co., Ltd., data molecular weight 2300-2800, hydroxyl group 0.8-1.0 mmol / g), 80.5 g of dimethylol propionic acid, 8 g of antioxidant 1010, and 100 g of acetone are added to a condenser equipped with an acetone reflux device and a discharge device. In a reactor of a pressure device, the temperature was raised to 85°C under nitrogen protection, 0.84g of dibutyltin dilaurate was added and reacted for 2h, and then 72.1g of 1,4-butanediol was added and continued to react at 80°C for 2h to obtain a polyurethane prepolymer, 23.2g of hydroxyethyl methacrylate was added to the polyurethane prepolymer and reacted at 80°C for 1h until the NCO content of the system was 0, and then 160g of acetone was added, and the viscosity of the system was adjusted to 5670mPa.s. After the reaction was completed, the temperature was lowered to 35°C, dimethylethanolamine was added to neutralize for 5min, and 800g of deionized water was added to disperse under high-speed shearing of a shear disperser to obtain an aqueous polyurethane resin emulsion;

[0091] Step 2, preparing a hydrocarbon phase solution: 180 g of styrene PS, 120 g of butadiene, 100 g of acrylonitrile, 10 g of butyl methacrylate, 36 g of sodium p-styrene sulfonate, 0.5 g of cumene hydroperoxide, 1 g of tert-dodecyl mercaptan, and 1000 g of deionized water are mixed and emulsified under high-speed shearing in a shear disperser to obtain an ABS emulsion;

[0092] Step 3: The waterborne polyurethane resin emulsion is heated to 85° C., and the ABS emulsion prepared in step 2 is added dropwise at a dropping speed of 50 g / min. After the addition is completed, the reaction is continued for 60 minutes until the styrene monomer concentration is lower than 0.1wt%. The temperature is lowered to 55° C., 1000 g of deionized water is added, and emulsified and dispersed under high-speed shearing of a shear disperser is performed. The acetone is then removed in vacuo to obtain a modified polyurethane dispersion. The average particle size of the emulsion is 400 nm. The emulsion is spray-dried to obtain a core-shell structure polyurethane toughening material.

[0093] Example 1: A high-strength and high-toughness composite plastic pallet is made of 30% high-density polyethylene HDPE (Shanghai Petrochemical Co., Ltd., China Petrochemical Corporation, brand: PE P5003D-B, batch number: SPS74525B1, density 0.9502 g / cm 3, melt mass flow rate MFR: 0.25g / 10min, tensile yield stress 23MPa), 2% linear low-density polyethylene LLDPE (Mobil LLDPE LL6201XR injection molding grade), 4% compatibilizer composition, 12% toughening agent composition, 4% toughening and reinforcing filler composition, 1.2% silicone masterbatch, 2% anti-aging additive, 0.8% CDM2022 / rheological masterbatch, the balance is polypropylene (Zhejiang Petrochemical Co., Ltd., brand K8003, product batch number: 20220816PP110517, melt mass flow rate (2.16kg, 230℃) 2.60g / 10min, tensile yield stress 22MPa, simple supported beam notched impact strength (23℃) 50kJ / m 2 ) is made.

[0094] The toughening agent composition is a core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 1.

[0095] The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH in a mass ratio of 1:1:0.02:0.08.

[0096] The toughening and reinforcing filler composition is an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm (Shanghai Fuding New Material Technology Co., Ltd., 50D / 20F ultra-high molecular weight polyethylene fiber cut to 4 mm, linear density 55Dtex, rupture modulus 1400-1600cn / dtex, density: 0.97-0.98g / cm 3 ), surface non-polar modified boron nitride whiskers, and surface magnetic ferroferric oxide grafted potassium titanate whiskers are composed in a mass ratio of 100:20:30.

[0097] The method for preparing the surface non-polar modified boron nitride whisker comprises the following steps:

[0098] S1. First, activate the boron nitride whiskers (diameter 0.5-2 μm, length 10-20 μm, brand Yamei Nano) by placing them in a muffle furnace and heating them to 280°C at 5°C / min for 1 hour, then naturally cooling them to room temperature for later use;

[0099] S2. The activated boron nitride whiskers are placed in a plasma treatment machine for low-temperature plasma treatment, the plasma treatment temperature is 4-6 ° C, the vacuum degree is set to 5Pa, the treatment gas is air, and the treatment time is 300s to obtain surface activated boron nitride whiskers;

[0100] S3. Weigh 10g of γ-glycidyloxypropyltrimethoxysilane KH560 and dissolve it in 490g of deionized water to prepare a 1.0w% KH560 aqueous solution. Add 5g of surface-activated boron nitride whiskers to 1kg of 1.0w% KH560 aqueous solution and stir mechanically for 5min to mix evenly. Then, heat to 75°C and perform ultrasonic dispersion treatment at an ultrasonic frequency of 40kHz and a power of 450W for 15min. Then, naturally cool to room temperature, vacuum filter the solid obtained, vacuum dry it, and dry it at 105°C for 2h to obtain surface-grafted epoxy-modified boron nitride whiskers.

[0101] S4. Dissolve 5 g of surface-grafted epoxy-modified boron nitride whiskers in 200 mL of DMF solvent, and add 2 g of lauric acid / DMP-30 mixture (10 g of lauric acid contains 0.2 g of DMP-30) at a dropping speed of 0.2 g / min at 65°C with magnetic stirring at 200 rpm. After the addition is completed, continue the reaction for 15 min. Use acetone to wash until neutral during vacuum filtration. The obtained solid is vacuum dried at 80°C for 3 h to obtain surface non-polar modified boron nitride whiskers.

[0102] The method for preparing potassium titanate whiskers with surface magnetic ferroferric oxide grafted thereon comprises the following steps:

[0103] S1. First, potassium titanate whiskers (diameter 0.2-0.5 μm, aspect ratio 20-30, CAS No. 12030-97-6, Hubei Yamade) were activated by placing them in a muffle furnace and heating them to 220°C at 5°C / min for 1 hour, then cooling them naturally to room temperature and setting them aside;

[0104] S2. Disperse 2 g of activated potassium titanate whiskers into 300 mL of deionized water to obtain a mixed solution A; dilute 3 mL of ferromagnetic fluid EMG 605 in 500 mL of water to obtain a mixed solution B; subject the mixed solution A to ultrasonic stirring using an ultrasonic stirrer, drop the mixed solution B into the mixed solution A at a dropping speed of 1 mL / min under ultrasonic stirring, subject the mixed solution to ultrasonic stirring at room temperature for 12 h, allow the solution to settle for 1 h, and observe whether the supernatant becomes clear and transparent; if the supernatant is turbid, it indicates that the magnetic ferroferric oxide has not been adsorbed; continue ultrasonic stirring at room temperature until the supernatant becomes clear and transparent, indicating that the magnetic ferroferric oxide has been adsorbed; centrifuge to obtain a solid; wash the solid with 500 mL of water, and dry it in an oven at 110° C. for 12 h; load the ferromagnetic nanoparticles onto the surface of the potassium titanate whiskers by electrostatic attraction and van der Waals forces to obtain potassium titanate whiskers with surface magnetic ferroferric oxide grafted thereon;

[0105] S3. Add 5g of potassium titanate whiskers with surface magnetic ferroferric oxide grafted thereon, 4g of KH550, and 500g of deionized water into a 1L beaker and mechanically mix for 5 minutes. Then use an ultrasonic agitator to perform ultrasonic dispersion treatment at an ultrasonic frequency of 40kHz and a power of 450W for 15 minutes. Naturally cool to room temperature, vacuum filter the obtained solid, and perform vacuum drying treatment at 105°C for 2 hours to obtain aminosilane-modified potassium titanate whiskers with surface magnetic ferroferric oxide grafted thereon.

[0106] The silicone masterbatch is composed of CMB1502 / polyethylene carrier silicone masterbatch and CMB1501 / polypropylene carrier silicone masterbatch in a mass ratio of 2:3. The anti-aging additives include antioxidants and anti-ultraviolet agents in a mass ratio of 1:1. The antioxidants are antioxidant 1076, antioxidant 168, and antioxidant 697 in a mass ratio of 10:1:1. The anti-ultraviolet agent is UV-622.

[0107] A method for preparing a high-strength and high-toughness composite plastic pallet comprises the following steps:

[0108] Step 1, accurately measuring high-density polyethylene HDPE, linear low-density polyethylene LLDPE, polypropylene PP, maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, maleic anhydride grafted polystyrene PS-g-MAH, core-shell structure polyurethane toughening material with PS as shell in Preparation Example 1, CMB1502 / polyethylene carrier silicone masterbatch, CMB1501 / polypropylene carrier silicone masterbatch, CDM2022 / rheological masterbatch, antioxidant 1076, antioxidant 168, antioxidant 697, UV-622, kneading at 165° C. for 300 s to obtain a plasticized fluidized mixture;

[0109] Ultra-high molecular weight polyethylene staple fibers (UHMTWPE) with a length of 4 mm, surface non-polar modified boron nitride whiskers, and surface aminosilane modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers were mixed in a mass ratio of 100:20:30 to obtain a toughening and reinforcing filler composition;

[0110] Step 2: Put the mixed material and the toughening and reinforcing filler composition into a twin-screw extruder for melt extrusion. The twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 175°C, the second temperature interval is set at 185°C, the third temperature interval is set at 195°C, the fourth temperature interval is set at 200°C, the fifth temperature interval is set at 200°C, the sixth temperature interval is set at 200°C, the seventh temperature interval is set at 200°C, and the die head temperature is 199.7°C. The obtained extruded melt is subjected to wire drawing, cooling, granulation, and drying to obtain a plastic pallet masterbatch with a particle size of 1.8-2.0 mm;

[0111] Step three, putting the plastic pallet masterbatch prepared in step two into a twin-screw extruder for melt extrusion, the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 195°C, the second temperature interval is set at 205°C, the third temperature interval is set at 215°C, the fourth temperature interval is set at 220°C, the fifth temperature interval is set at 225°C, the sixth temperature interval is set at 225°C, the seventh temperature interval is set at 225°C, the die head temperature is 224.8°C, the obtained melt extrusion is injected into the molding mold, the injection pressure is 85MPa, the holding pressure is 32% of the injection pressure, the back pressure is 18MPa, the injection time is 3s, the holding time is 90s, the cooling time is 90s, the temperature of the molding mold is controlled at 145°C, a magnetic field is applied, the magnetic field strength is 500mT, the magnetic field direction is relatively perpendicular to the horizontal plane of the molding mold, the magnetic field holding time is 2h, and it is naturally cooled to room temperature under the action of the magnetic field to obtain a semi-finished pallet with a molding mold;

[0112] Step 4: Heat treat the semi-finished pallet in the molding mold in step 3 to eliminate internal stress. Apply a magnetic field with a magnetic field strength of 800mT. The direction of the magnetic field is relatively perpendicular to the horizontal plane of the molding mold. Heat the temperature to 105°C at 0.8°C / min for 45 minutes. Open the furnace and cool naturally to room temperature. Remove the magnetic field, demould, trim the burrs, and grind to obtain the finished plastic pallet.

[0113] The difference between Example 2 and Example 1 is that the toughening agent composition is the core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 1, which is replaced by the toughening agent composition is the core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 2.

[0114] The difference between Example 3 and Example 1 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and a surface coated with PS resin modified, boron nitride whiskers with non-polar surface modifications, and aminosilane-modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers in a mass ratio of 100:20:30.

[0115] The preparation method of the surface-coated PS resin modified ultra-high molecular weight polyethylene staple fiber is as follows: PS resin (polystyrene resin PS 525GPPS transparent grade, Jining Tangyi Chemical Co., Ltd.) is put into a twin-screw extruder, and the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 170°C, the second temperature interval is set at 180°C, the third temperature interval is set at 190°C, the fourth temperature interval is set at 195°C, the fifth temperature interval is set at 195°C, the sixth temperature interval is set at 195°C, the seventh temperature interval is set at 195°C, and the die head temperature is 194.6°C. The molten extrudate is attached to the ultra-high molecular weight polyethylene fiber (Shanghai Fuding New Material Technology Co., Ltd., specification: 50D / 20F, linear density 55Dtex, rupture modulus 1400-1600cn / dtex, density: 0.97-0.98g / cm 3 ))'s outer surface, water-cooled and dried to obtain a finished product surface-coated PS resin-modified ultra-high molecular weight polyethylene long fiber, and the finished product surface-coated PS resin-modified ultra-high molecular weight polyethylene long fiber was cut into surface-coated PS resin-modified ultra-high molecular weight polyethylene short fibers with a length of 4 mm.

[0116] The difference between Example 4 and Example 3 is that the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and surface-coated with PS resin modified are replaced by ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2 mm and surface-coated with PS resin modified.

[0117] The difference between Example 5 and Example 3 is that the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and surface-coated with PS resin modified are replaced by ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 6 mm and surface-coated with PS resin modified.

[0118] The difference between Example 6 and Example 1 is that the surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm is replaced by a composition formed by an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2 mm, an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm, and an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 6 mm, and the mass ratio of the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2 mm, the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm, and the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 6 mm is 1:2:5.

[0119] The difference between Example 7 and Example 1 is that a high-strength and high-toughness composite plastic pallet is made of 30% high-density polyethylene HDPE, 4% compatibilizer composition, 4% toughening agent composition, 12% toughening and reinforcing filler composition, 1.2% silicone masterbatch, 2% anti-aging additive, 0.8% CDM2022 / rheological masterbatch, and the balance is polypropylene PP. The toughening agent composition is a core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 1.

[0120] The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH and maleic anhydride grafted polystyrene PS-g-MAH in a mass ratio of 1:1:0.1.

[0121] The difference between Example 8 and Example 3 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and a surface coated with PS resin modified, boron nitride whiskers with non-polar surface modifications, and aminosilane-modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers in a mass ratio of 100:10:10.

[0122] The difference between Example 9 and Example 3 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and a surface coated with PS resin modified, boron nitride whiskers with non-polar surface modifications, and aminosilane-modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers in a mass ratio of 100:30:50.

[0123] The difference between Example 10 and Example 3 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modifications, and aminosilane-modified potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface, with a mass ratio of 100:20:30.

[0124] The method for preparing potassium titanate whiskers with non-polar surface modification comprises the following steps:

[0125] S1. The potassium titanate whiskers are first activated by placing them in a muffle furnace and heating them to 220°C at 5°C / min for 1 hour, then cooling them naturally to room temperature for later use;

[0126] S2. The activated potassium titanate whiskers are placed in a plasma treatment machine for low-temperature plasma treatment, the plasma treatment temperature is 4-6 ° C, the vacuum degree is set to 5Pa, the treatment gas is air, the treatment time is 300s, and the surface activated boron nitride whiskers are obtained;

[0127] S3. Weigh 10g of γ-glycidyloxypropyltrimethoxysilane KH560 and dissolve it in 490g of deionized water to prepare a 1.0w% KH560 aqueous solution. Add 5g of surface-activated potassium titanate whiskers to 1kg of 1.0w% KH560 aqueous solution and stir mechanically for 5min to mix evenly. Then, heat to 75°C and perform ultrasonic dispersion treatment at an ultrasonic frequency of 40kHz and a power of 450W for 15min. Then, naturally cool to room temperature, vacuum filter the solid and perform vacuum drying. Dry at 105°C for 2h to obtain surface-grafted epoxy-modified potassium titanate whiskers.

[0128] S4. Dissolve 5 g of surface-grafted epoxy-modified potassium titanate whiskers in 200 mL of DMF solvent, add 2 g of lauric acid / DMP-30 mixture (10 g of lauric acid contains 0.2 g of DMP-30) at a dropping rate of 0.2 g / min at 65°C with magnetic stirring at 200 rpm. Continue to react for 15 min after the addition is completed. Use acetone to wash until neutral during vacuum filtration. Vacuum dry the solid and dry it at 80°C for 3 h to obtain surface non-polar modified potassium titanate whiskers.

[0129] The difference between Example 11 and Example 1 is that the toughening agent composition is a core-shell polyurethane toughening material with ABS as the shell in Preparation Example 3. The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH in a mass ratio of 1:1:0.02:0.08.

[0130] The difference between Example 12 and Example 1 is that the toughening agent composition is a core-shell polyurethane toughening material with ABS as the shell in Preparation Example 4. The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH in a mass ratio of 1:1:0.02:0.08.

[0131] The difference between Example 13 and Example 11 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm and a surface coated with ABS resin modified, boron nitride whiskers with non-polar surface modifications, and aminosilane-modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers in a mass ratio of 100:20:30.

[0132] The preparation method of the surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fiber is as follows: ABS resin (SABIC's ABSDL100, purchased by Dongguan Yuming Plastic Technology Co., Ltd.) is put into a twin-screw extruder, the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 195°C, the second temperature interval is set at 210°C, the third temperature interval is set at 220°C, the fourth temperature interval is set at 230°C, the fifth temperature interval is set at 235°C, the sixth temperature interval is set at 235°C, the seventh temperature interval is set at 235°C, the die head temperature is 234.7°C, and the molten extrudate is attached to an ultra-high molecular weight polyethylene fiber (Shanghai Fuding New Material Technology Co., Ltd., specification: 50D / 20F, linear density 55Dtex, rupture modulus 1400-1600cn / dtex, density: 0.97-0.98g / cm 3 ), water-cooled and dried to obtain a finished product surface-coated PS resin-modified ultra-high molecular weight polyethylene long fiber, and the finished product surface-coated ABS resin-modified ultra-high molecular weight polyethylene long fiber was cut into 4 mm long surface-coated PS resin-modified ultra-high molecular weight polyethylene short fibers.

[0133] The difference between Example 14 and Example 1 is that the toughening agent composition is composed of the core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 1 and the core-shell structure polyurethane toughening material with ABS as the shell in Preparation Example 3 in a mass ratio of 1:1.

[0134] The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH in a mass ratio of 1:1:0.1:0.1.

[0135] The difference between Example 15 and Example 1 is that the toughening agent composition is composed of the core-shell structure polyurethane toughening material with PS as the shell in Preparation Example 2 and the core-shell structure polyurethane toughening material with ABS as the shell in Preparation Example 4 in a mass ratio of 1:1.

[0136] The compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH in a mass ratio of 1:1:0.1:0.1.

[0137] The difference between Example 16 and Example 15 is that the toughening and reinforcing filler composition is composed of the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm and surface-coated ABS resin modified in Example 13, the surface non-polar modified potassium titanate whiskers prepared in Example 10, and the aminosilane-modified surface magnetic ferroferric oxide grafted potassium titanate whiskers prepared in Example 1, with a mass ratio of 100:20:30.

[0138] The difference between Example 17 and Example 15 is that the toughening and reinforcing filler composition is composed of the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm and the surface coated with PS resin modified in Example 3, the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm and the surface coated with ABS resin modified in Example 13, the surface non-polar modified potassium titanate whiskers prepared in Example 10, and the aminosilane-modified surface magnetic ferroferric oxide grafted potassium titanate whiskers prepared in Example 1, with a mass ratio of 50:50:20:30.

[0139] The difference between Example 18 and Example 3 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers with a length of 4 mm and a surface coated with PS resin modified, boron nitride whiskers with non-polar surface modifications, potassium titanate whiskers with aminosilane-modified surface magnetic ferrosoferric oxide grafted, and ABS@PU@zinc oxide whiskers in a mass ratio of 10:2:3:1.

[0140] The preparation method of ABS@PU@zinc oxide whiskers is as follows:

[0141] S1. First, the zinc oxide whiskers (diameter 0.5-5μm, length 10-50μm, true density 5.3±0.2g / cm 3 , four-needle zinc oxide whisker, CAS No. 1344-2-2, brand Chaotai) was activated: placed in a muffle furnace and heated to 180°C at 5°C / min for 1h, cooled naturally to room temperature, and set aside;

[0142] S2. The activated zinc oxide whiskers are placed in a plasma treatment machine for low-temperature plasma treatment, the plasma treatment temperature is 4-6 ° C, the vacuum degree is set to 5Pa, the treatment gas is air, and the treatment time is 300s to obtain surface activated zinc oxide whiskers;

[0143] S3. 513 g of MDI, 67.1 g of dimethylol propionic acid, 400 g of polycarbonate diol CD220 (molecular weight 2000, Daicel Corporation of Japan), 600 g of polyethylene adipate diol (molecular weight 2000, Zhejiang Hexin Technology Co., Ltd.), 67.1 g of dimethylol propionic acid, 8 g of antioxidant 1010, and 100 g of acetone were added to a reactor equipped with an acetone condensation reflux device and a pressure relief device, and the temperature was raised to 85 ° C under nitrogen protection, and 0.84 g of February was added. Dibutyltin cinnamate was reacted for 2 hours, and then 106.4g of 1,6-hexanediol was added to continue to react at 80°C for 2 hours to obtain a polyurethane prepolymer, 13.1g of hydroxyethyl methacrylate was added to the polyurethane prepolymer and reacted at 80°C for 1 hour, and then 175g of acetone was added, and the system viscosity was adjusted to 5260mPa.s. After the reaction was completed, the temperature was lowered to 35°C, dimethylethanolamine was added to neutralize for 5 minutes, and 800g of deionized water was added to disperse under high-speed shearing of a shear disperser to obtain an aqueous polyurethane resin emulsion;

[0144] 170 g of styrene PS, 120 g of butadiene, 110 g of acrylonitrile, 12 g of butyl methacrylate, 36 g of sodium p-styrene sulfonate, 0.8 g of cumene hydroperoxide, 1.2 g of tert-dodecyl mercaptan, and 1000 g of deionized water were mixed and emulsified under high-speed shearing in a shear disperser to prepare an ABS emulsion;

[0145] S4. Weigh 200g of waterborne polyurethane resin emulsion. Add 5g of surface activated zinc oxide whisker in S2 and 0.2g of inhibitor methyl hydroquinone THQ and mix evenly to obtain a mixed solution. After the obtained mixed solution is heated to 75°C, it is reacted for 0.5h under magnetic stirring at 320rpm. The surface active functional groups of the surface activated zinc oxide whisker react with NCO in the polyurethane latex particles to obtain PU@zinc oxide whisker; then, the ABS emulsion prepared in step 3 is added dropwise at a dropwise speed of 50g / min. After the addition is completed, the reaction is continued for 1h until the concentration of styrene monomer is lower than 0.1wt%, and the temperature is lowered to 55°C. 1000g of deionized water is added, and emulsified and dispersed under high-speed shearing of a shear disperser, and then the acetone is removed in vacuo to obtain a mixed emulsion, and the mixed emulsion is spray-dried to obtain ABS@PU@zinc oxide whisker.

[0146] The difference between Example 19 and Example 13 is that the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers with a length of 4 mm and surface-coated ABS resin modified, surface non-polar modified boron nitride whiskers, aminosilane-modified surface magnetic ferrosoferric oxide grafted potassium titanate whiskers, and ABS@PU@zinc oxide whiskers in a mass ratio of 10:2:3:1.

[0147] The difference between Example 20 and Example 17 is that the toughening and reinforcing filler composition is composed of the ultra-high molecular weight polyethylene staple fiber with a length of 4 mm and the surface coated with PS resin modified in Example 3, the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 4 mm and the surface coated with ABS resin modified in Example 13, the surface non-polar modified potassium titanate whiskers prepared in Example 10, the aminosilane-modified surface magnetic ferroferric oxide grafted potassium titanate whiskers prepared in Example 1, and ABS@PU@zinc oxide whiskers in a mass ratio of 5:5:2:3:1.

[0148] The difference between Comparative Example 1 and Example 1 is that no toughening and reinforcing filler composition is added to the plastic pallet formula.

[0149] A high-strength and high-toughness composite plastic pallet is made of 30% high-density polyethylene HDPE, 2% linear low-density polyethylene LLDPE, 4% compatibilizer composition, 12% toughening agent composition, 1.2% silicone masterbatch, 2% anti-aging additive, 0.8% CDM2022 / rheological masterbatch, and the balance is polypropylene PP.

[0150] The difference between Comparative Example 2 and Example 1 is that no toughening agent composition is added to the formula of the plastic pallet.

[0151] A high-strength and high-toughness composite plastic pallet is made of 30% high-density polyethylene HDPE, 2% linear low-density polyethylene LLDPE, 4% compatibilizer composition, 4% toughening and reinforcing filler composition, 1.2% silicone masterbatch, 2% anti-aging additive, 0.8% CDM2022 / rheological masterbatch, and the balance is polypropylene PP.

[0152] The difference between Comparative Example 3 and Example 1 is that the toughening agent composition and the toughening and reinforcing filler composition are not added to the plastic pallet formula. Specifically, a high-strength and high-toughness composite plastic pallet is made of 30% high-density polyethylene HDPE, 2% linear low-density polyethylene LLDPE, 4% compatibilizer composition, 1.2% silicone masterbatch, 2% anti-aging additive, 0.8% CDM2022 / rheological masterbatch, and the balance is polypropylene PP.

[0153] The difference between Comparative Example 4 and Example 1 is that the toughening agent composition is polyurethane TPU (1180A10 BASF TPU).

[0154] The difference between Comparative Example 5 and Example 1 is that the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH and maleic anhydride grafted polypropylene PP-g-MAH in a mass ratio of 1:1:.

[0155] The difference between Comparative Example 6 and Example 1 is that the toughening and reinforcing filler composition is ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm.

[0156] A method for preparing a high-strength and high-toughness composite plastic pallet comprises the following steps:

[0157] Step 1, accurately measuring high-density polyethylene HDPE, linear low-density polyethylene LLDPE, polypropylene PP, maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, maleic anhydride grafted polystyrene PS-g-MAH, core-shell structure polyurethane toughening material with PS as shell in Preparation Example 1, CMB1502 / polyethylene carrier silicone masterbatch, CMB1501 / polypropylene carrier silicone masterbatch, CDM2022 / rheological masterbatch, antioxidant 1076, antioxidant 168, antioxidant 697, UV-622, kneading at 165° C. for 270 seconds, adding ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 4 mm, and kneading for 30 seconds to obtain a plasticized fluidized mixture;

[0158] Step 2, putting the mixed material into a twin-screw extruder for melt extrusion, the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 175°C, the second temperature interval is set at 185°C, the third temperature interval is set at 195°C, the fourth temperature interval is set at 200°C, the fifth temperature interval is set at 200°C, the sixth temperature interval is set at 200°C, the seventh temperature interval is set at 200°C, the die head temperature is 199.8°C, and the obtained extruded melt is subjected to wire drawing, cooling, granulation, and drying to obtain plastic pallet masterbatch with a particle size of 1.8-2.0 mm;

[0159] Step three, putting the plastic pallet masterbatch prepared in step two into a twin-screw extruder for melt extrusion, the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 195°C, the second temperature interval is set at 205°C, the third temperature interval is set at 215°C, the fourth temperature interval is set at 220°C, the fifth temperature interval is set at 225°C, the sixth temperature interval is set at 225°C, the seventh temperature interval is set at 225°C, the die head temperature is 224.7°C, the obtained melt extrusion is injected into the molding mold, the injection pressure is 85MPa, the holding pressure is 32% of the injection pressure, the back pressure is 18MPa, the injection time is 3s, the holding time is 90s, the cooling time is 90s, the temperature of the molding mold is controlled at 40°C, and it is naturally cooled to room temperature to obtain a semi-finished pallet with a molding mold;

[0160] Step 4: heat treat the semi-finished pallet in the molding mold of step 3 to eliminate internal stress, heat it to 105°C at 0.8°C / min for 45 minutes, open the furnace and naturally cool it to room temperature, demould, trim the burrs, and grind it to obtain the finished plastic pallet.

[0161] The difference between Comparative Example 7 and Example 1 lies in the difference between step 3 and step 4 in the method for preparing a plastic pallet, specifically:

[0162] Step three, putting the plastic pallet masterbatch prepared in step two into a twin-screw extruder for melt extrusion, the twin-screw extruder has seven heating temperature intervals, the first temperature interval is set at 195°C, the second temperature interval is set at 205°C, the third temperature interval is set at 215°C, the fourth temperature interval is set at 220°C, the fifth temperature interval is set at 225°C, the sixth temperature interval is set at 225°C, the seventh temperature interval is set at 225°C, the die head temperature is 224.8°C, the obtained melt extrusion is injected into the molding mold, the injection pressure is 85MPa, the holding pressure is 32% of the injection pressure, the back pressure is 18MPa, the injection time is 3s, the holding time is 90s, the cooling time is 90s, the temperature of the molding mold is controlled at 40°C, and it is naturally cooled to room temperature to obtain a semi-finished pallet with a molding mold;

[0163] Step 4: heat treat the semi-finished pallet in the molding mold of step 3 to eliminate internal stress, heat it to 105°C at 0.8°C / min for 45 minutes, open the furnace and naturally cool it to room temperature, demould, trim the burrs, and grind it to obtain the finished plastic pallet.

[0164] The difference between Comparative Example 8 and Example 3 is that the ultra-high molecular weight polyethylene staple fibers with a length of 4 mm and surface-coated PS resin-modified are replaced by ultra-high molecular weight polyethylene staple fibers with a length of 1.0 mm and surface-coated PS resin-modified.

[0165] Table 1: Test parameter table of plastic pallet masterbatch in Examples 1-20 and Comparative Examples 1-8

[0166]

[0167]

[0168] Note: Performance test in Table 1: 1. Density is measured by MDJ-300S electronic direct-reading plastic particle density meter. 2. Tensile strength test method: According to GB / T 1040.1-2018 Determination of tensile properties of plastics. 3. Flexural elastic modulus test method: According to GB / T 9341-2008 "Determination of flexural properties of plastics". 4. Impact toughness test method: Prepare the sample, the sample is a long strip sample of 80mm×10mm×4mm, and use the method of GB / T 12670-2008 polypropylene resin to measure the simply supported beam notched impact strength at 23℃.

[0169] Combining Example 1 and Comparative Examples 1-3 with Table 1, it can be seen that the plastic pallet masterbatch prepared by the formula provided in this application has good mechanical properties and impact temperature resistance, and the overall density is less than 1.0 g / cm 3 , to meet the lightweight needs.

[0170] It can be seen from Example 1 and Comparative Example 4 and Table 1 that the plastic pallet masterbatch prepared using the core-shell structured polyurethane material prepared in the present application has better mechanical properties and impact temperature resistance, which facilitates the uniform distribution of the core-shell structured polyurethane material in the matrix resin, thereby achieving better toughening and reinforcement.

[0171] It can be seen from Example 1, Example 7 and Comparative Example 5 and Table 1 that when linear low-density polyethylene LLDPE is added to the formula, the mechanical properties and impact toughness of the prepared plastic pallet masterbatch can be improved to a certain extent. When linear low-density polyethylene LLDPE is added to the formula, but linear low-density polyethylene LLDPE-g-MAH is not added to the compatibilizer composition, the mechanical properties and impact toughness of the prepared plastic pallet masterbatch are negatively affected. Therefore, when linear low-density polyethylene LLDPE is added to the formula, the compatibilizer composition contains LLDPE-g-MAH.

[0172] Combining Example 1 and Comparative Example 6 with Table 1, it can be seen that although the ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm can also play a certain reinforcing and toughening effect, in actual consideration of the load capacity of the prepared plastic pallet and the stability of the finished product, the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and surface-coated ABS resin modified, and ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified. The plastic pallet masterbatch prepared by combining at least one of the following: surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes. The plastic pallet masterbatch prepared by injection molding of the plastic pallet masterbatch has better mechanical properties and impact temperature resistance. The plastic pallet prepared by injection molding of the plastic pallet masterbatch has better stacking limit load performance and longer service life.

[0173] It can be seen from Example 1 and Comparative Example 7 and Tables 1-2 that the setting of the magnetic field in the preparation method provided in the present application adjusts the radial direction of the surface magnetic ferroferric oxide grafted inorganic material, which can effectively improve the overall stacking limit load performance and static / dynamic load capacity of the plastic pallet while ensuring the excellent mechanical strength and impact resistance of the plastic pallet.

[0174] It can be seen from Example 1 and Example 3 and Table 1 that the plastic pallet masterbatch prepared from ultra-high molecular weight polyethylene staple fibers modified by PS resin coated on the surface has better mechanical strength and impact resistance than the plastic pallet masterbatch prepared from ultra-high molecular weight polyethylene staple fibers not modified by PS resin coated on the surface.

[0175] It can be seen from Examples 3-5 and Comparative Example 8 and Table 1 that the length of the ultra-high molecular weight polyethylene staple fibers modified by the surface-coated PS resin is preferably controlled to be 2-6 mm. Preferably, the length of the ultra-high molecular weight polyethylene staple fibers modified by the surface-coated PS resin is controlled to be 4-6 mm. A length less than 2 mm will affect the overall mechanical properties, while a length too long will affect the processing performance.

[0176] It can be seen from Examples 3-5 and 6 and Table 1 that the plastic pallet masterbatch prepared by mixing ultra-high molecular weight polyethylene staple fibers modified by surface-coated PS resin of different lengths has better mechanical property advantages.

[0177] In combination with Examples 1-20 and Comparative Examples 1-8 and the test parameters of Table 1, the plastic pallet masterbatch in Examples 1 and 3, the plastic pallet masterbatch in Example 13, the plastic pallet masterbatch in Examples 17-20, the plastic pallet masterbatch in Comparative Example 3, and the plastic pallet masterbatch in Comparative Example 7 are preferably selected to prepare finished plastic pallet samples (network field-shaped plastic pallets, sample size 1100mmX1100mmx150mm, single-sided use, four-way fork), and the following performance tests are performed.

[0178] Performance test of finished plastic pallet samples: 1. The ultimate load in the fork lift test is measured in accordance with GB / T 4995-2014 "Performance requirements and test selection for intermodal general flat pallets" and GB / T 4996-2014 "Test methods for intermodal general flat pallets", and the test environment is 17℃, 43%RH. 2. The ultimate load in the stacking test is measured in accordance with GB / T 4995-2014 and GB / T4996-2014, and the test environment is 17℃, 39%RH. 3. The ultimate load in the bottom deck bending test is measured in accordance with GB / T4995-2014 and GB / T 4996-2014, and the test environment is 21℃, 13%RH. 4. The diagonal change rate in the corner drop test is measured in accordance with GB / T 4995-2014 and GB / T 4996-2014, and the test environment is 20℃, 43%RH. 5. Shear impact test is carried out in accordance with GB / T4995-2014 and GB / T 4996-2014, with the test environment at 19°C and 26%RH.

[0179] Table 2: Test parameters of finished plastic pallets in Example 1, Example 3, Examples 17-20 and Comparative Examples 3 and 7

[0180]

[0181] It can be seen from Examples 1-20 and Comparative Examples 1-8 and Table 1-2 that the plastic pallets in the present application have a low density, meet the lightweight requirements, and have the advantages of high stacking limit load and impact resistance, which can increase the amount of cargo transported per day, thereby improving the logistics level and promoting economic development.

[0182] From Example 1 and Comparative Example 7 and Tables 1-2, it can be seen that the setting of the magnetic field in the preparation method provided in the present application adjusts the radial direction of the surface magnetic ferroferric oxide grafted inorganic material. Although there is a certain attenuation on the mechanical strength and impact resistance of the plastic pallet, the overall mechanical strength and impact resistance are still relatively excellent. In addition, the radial direction of the surface magnetic ferroferric oxide grafted inorganic material can effectively improve the overall stacking limit load performance and static / dynamic load capacity of the plastic pallet. That is, when using the plastic pallet in the present application, the overall cargo carrying capacity can be improved under a constant freight volume.

[0183] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength and high-toughness composite plastic pallet, characterized by: It is made of the following raw materials in percentage by mass: 20-40% high-density polyethylene HDPE, 0-5% linear low-density polyethylene LLDPE, 3-6% compatibilizer composition, 5-20% toughening agent composition, 1-5% toughening and reinforcing filler composition, 0.5-2% silicone masterbatch, 1-3% anti-aging additive, 0.5-1.0% rheological masterbatch, and the balance is polypropylene PP; The compatibilizer composition is at least one of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted linear low-density polyethylene LLDPE-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH; The toughening agent composition is a core-shell structured polyurethane, wherein the shell of the core-shell structured polyurethane is one or a combination of acrylonitrile-styrene-butadiene copolymer ABS and maleic anhydride grafted polystyrene PS, and the core is polyurethane PU; The toughening and reinforcing filler composition comprises at least one of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with ABS resin modified, and ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated with PS resin modified, in combination with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, surface non-polar modified zinc oxide whiskers, surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

2. The high-strength and high-toughness composite plastic pallet according to claim 1, characterized in that: When the core-shell polyurethane is acrylonitrile-styrene-butadiene copolymer ABS, the compatibilizer composition is maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH; When the core-shell polyurethane is polystyrene PS, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH; When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, or maleic anhydride grafted polystyrene PS-g-MAH.

3. The high-strength and high-toughness composite plastic pallet according to claim 2, characterized in that: When the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, the mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2); When the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH, the mass ratio of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.05-0.2); When the compatibilizer composition is composed of maleic anhydride grafted polyethylene HDPE-g-MAH, maleic anhydride grafted polypropylene PP-g-MAH, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and maleic anhydride grafted polystyrene PS-g-MAH, the mass ratio of the maleic anhydride grafted polyethylene HDPE-g-MAH, the maleic anhydride grafted polypropylene PP-g-MAH, the maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer ABS-g-MAH, and the maleic anhydride grafted polystyrene PS-g-MAH is (0.8-1.2):(0.8-1.2):(0.02-0.10):(0.02-0.10).

4. The high-strength and high-toughness composite plastic pallet according to claim 2, characterized in that: When the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition includes at least one of a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface non-polar modified boron nitride whisker, a surface non-polar modified potassium titanate whisker, a surface non-polar modified zinc oxide whisker, a surface magnetic ferroferric oxide grafted boron nitride whisker, a surface magnetic ferroferric oxide grafted potassium titanate whisker, a surface magnetic ferroferric oxide grafted zinc oxide whisker, and a surface magnetic ferroferric oxide grafted halloysite nanotube; When the shell of the core-shell polyurethane is polystyrene PS, the toughening and reinforcing filler composition includes at least one of the following: an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified surface, a surface-nonpolar modified boron nitride whisker, a surface-nonpolar modified potassium titanate whisker, a surface-nonpolar modified zinc oxide whisker, a surface-magnetic ferroferric oxide grafted boron nitride whisker, a surface-magnetic ferroferric oxide grafted potassium titanate whisker, a surface-magnetic ferroferric oxide grafted zinc oxide whisker, and a surface-magnetic ferroferric oxide grafted halloysite nanotube; When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes at least one of a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, a surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, and a surface non-polar modified boron nitride whisker, a surface non-polar modified potassium titanate whisker, a surface non-polar modified zinc oxide whisker, a surface magnetic ferroferric oxide grafted boron nitride whisker, a surface magnetic ferroferric oxide grafted potassium titanate whisker, a surface magnetic ferroferric oxide grafted zinc oxide whisker, and a surface magnetic ferroferric oxide grafted halloysite nanotube.

5. The high-strength and high-toughness composite plastic pallet according to claim 4, characterized in that: When the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition includes at least one of surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface-nonpolar modified boron nitride whiskers, surface-nonpolar modified potassium titanate whiskers, and surface-nonpolar modified zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted boron nitride whiskers, surface-magnetic ferroferric oxide-grafted potassium titanate whiskers, surface-magnetic ferroferric oxide-grafted zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted halloysite nanotubes; When the shell of the core-shell polyurethane is polystyrene PS, the toughening and reinforcing filler composition includes at least one of surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface-nonpolar modified boron nitride whiskers, surface-nonpolar modified potassium titanate whiskers, and surface-nonpolar modified zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted boron nitride whiskers, surface-magnetic ferroferric oxide-grafted potassium titanate whiskers, surface-magnetic ferroferric oxide-grafted zinc oxide whiskers, and surface-magnetic ferroferric oxide-grafted halloysite nanotubes; When the toughening agent composition is composed of a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes an ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated ABS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm and a surface-coated PS resin-modified ultra-high molecular weight polyethylene staple fiber UHMTWPE with a length of 2-6 mm, in combination with at least one of surface non-polar modified boron nitride whiskers, surface non-polar modified potassium titanate whiskers, and surface non-polar modified zinc oxide whiskers, in combination with at least one of surface magnetic ferroferric oxide grafted boron nitride whiskers, surface magnetic ferroferric oxide grafted potassium titanate whiskers, surface magnetic ferroferric oxide grafted zinc oxide whiskers, and surface magnetic ferroferric oxide grafted halloysite nanotubes.

6. The high-strength and high-toughness composite plastic pallet according to claim 5, characterized in that: When the core-shell polyurethane shell is acrylonitrile-styrene-butadiene copolymer ABS, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface; When the core-shell polyurethane shell is polystyrene PS, the toughening and reinforcing filler composition comprises ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface; When the toughening agent composition is a polyurethane with a core-shell structure having an acrylonitrile-styrene-butadiene copolymer ABS as the shell, or a polyurethane with a core-shell structure having a polystyrene PS as the shell, the toughening and reinforcing filler composition includes ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with ABS resin modified, ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and a surface coated with PS resin modified, potassium titanate whiskers with non-polar surface modifications, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface.

7. The high-strength and high-toughness composite plastic pallet according to claim 6, characterized in that: When the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and modified by ABS resin on the surface, potassium titanate whiskers with non-polar surface modifications, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface, the mass ratio of the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and modified by ABS resin on the surface, the potassium titanate whiskers with non-polar surface modifications, and the potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface is 100:(10-30):(10-50); When the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface, the mass ratio of the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified, potassium titanate whiskers with non-polar surface modification, and potassium titanate whiskers with magnetic ferrosoferric oxide grafted on the surface is 100:(10-30):(10-50); When the toughening and reinforcing filler composition is composed of ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated PS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, surface non-polar modified potassium titanate whiskers, and surface magnetic ferroferric oxide grafted potassium titanate whiskers, the mass ratio of the ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm and surface-coated ABS resin modified ultra-high molecular weight polyethylene staple fibers UHMTWPE with a length of 2-6 mm, the surface non-polar modified potassium titanate whiskers, and the surface magnetic ferroferric oxide grafted potassium titanate whiskers is (40-60):(40-60):(10-30):(10-50).

8. The high-strength and high-toughness composite plastic pallet according to claim 1, characterized in that: The toughening and reinforcing filler composition also includes ABS@PU@inorganic whiskers, and the inorganic whiskers in the ABS@PU@inorganic whiskers include at least one of boron nitride whiskers, surface potassium titanate whiskers, zinc oxide whiskers, zirconium oxide whiskers, silicon carbide whiskers, and calcium carbonate whiskers.

9. The high-strength and high-toughness composite plastic pallet according to claim 1, characterized in that: The silicone masterbatch is at least one of CMB1502 / polyethylene carrier silicone masterbatch, CMB1501 / polypropylene carrier silicone masterbatch, and CMB901 / automotive interior PP scratch-resistant masterbatch; the rheological masterbatch is CDM2022 / rheological masterbatch; the anti-aging additive includes an antioxidant and an anti-ultraviolet agent, and the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 1024 combined with at least one of antioxidant 168 and antioxidant 697; the anti-ultraviolet agent is at least one of UV-531, UV-234, and UV-622.

10. A method for preparing a high-strength and high-toughness composite plastic pallet according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, placing accurately measured high-density polyethylene, linear low-density polyethylene, compatibilizer composition, toughening agent composition, silicone masterbatch, rheological masterbatch, polypropylene, and anti-aging additive at 160-165° C. and kneading for 240-320 seconds to obtain a mixture; Step 2: Put the mixture and the toughening and reinforcing filler composition into a twin-screw extruder for melt extrusion, wire drawing, cooling, granulation, and drying to obtain a plastic pallet masterbatch with a particle size of 0.5-2.0 mm; Step 3: Put the plastic pallet masterbatch into a twin-screw extruder for melt extrusion, and inject the obtained melt extrusion into a molding die. The temperature of the molding die is controlled at 140-160°C, and a magnetic field is applied. The magnetic field strength is 300-1200mT, and the direction of the magnetic field is relatively perpendicular to the horizontal plane of the molding die. The magnetic field holding time is 2-8h, and the semi-finished pallet is naturally cooled to room temperature to obtain a semi-finished pallet; Step 4: heat treat the semi-finished pallet in the molding mold of step 3 to eliminate internal stress. Apply a magnetic field with a magnetic field strength of 300-1200mT. The direction of the magnetic field is relatively perpendicular to the horizontal plane of the molding mold. Heat the temperature to 80-120℃ at a rate of 0.5-1℃ / min for 0.5-1h. Open the furnace and cool naturally to room temperature. Demould, trim burrs, and grind to obtain a finished plastic pallet.

Citation Information

Patent Citations

  • A creep-resistant polypropylene, its preparation method, and a plastic pallet

    CN113549291B